Study on exogenous application of thidiazuron on seed size of Brassica napus L. - Zhai, Lu; Xie, Lingli; Xu, JinSong; Xu, Benbo; Dong, Jing; Zhang, XueKun (Frontiers in Plant Science, 2022)
Thidiazuron (TDZ) is a novel and efficient cytokinin commonly used in tissue culture, and numerous studies have demonstrated that TDZ can increase berry size. However, no study to date has explored the effect of TDZ on seed size of Brassica napus and the mechanism. To shed light on the effect of TDZ on the seed size of B. napus, four different concentrations of TDZ were applied to B. napus. Results indicated that TDZ treatment could increase the seed diameter and silique length of B. napus to varying degrees and 100 µmol/L and 200 µmol/L TDZ treatments were the most effective with a 3.6% and 4.6% increase in seed diameter, respectively. In addition, the yield of B. napus was also substantially increased under TDZ treatment. On the other hand, confocal micrographs of embryos and cotyledon cells suggested that embryos and their cotyledon epidermal cells treated with 200 µmol/L TDZ were obviously larger in size than the control. Furthermore, TDZ promoted the upregulation of some key maternal tissue growth-related genes, including two G-protein signaling genes (AGG3 and RGA1) and two transcriptional regulators (ANT and GS2). The expression analysis of genes related to the auxin metabolic pathways, G-protein signaling, endosperm growth and transcriptional regulators confirmed that treatment with TDZ negatively regulated the key genes ABI5, AGB1, AP2, ARF2 and ARF18 during bud development stage and florescence. The results strongly suggested that TDZ might regulate the transcriptional levels of key genes involved in auxin metabolic pathways, G-protein signaling, endosperm growth and transcriptional regulators, which resulted in bigger cotyledon epidermal cells and seed size in B. napus. This study explored the mechanism of TDZ treatment on the seed size of B. napus and provided an important reference for improving rapeseed yield.